(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose - Mathematical literacy and mathematical problemsolving are crucial abilities that link mathematics content to real life applications, facilitating both mathematics understanding and mathematical processes. The present study aimed to investigate the effectiveness of the STEMEN (STEM and educational neuroscience) teaching model in enhancing mathematical literacy and problem-solving skills. Methodology - This study adopted a pre-test and post-test control group design. Among 156 Grade 9 students from a secondary school in Phayao, Thailand, 70 were randomly selected. The STEMEN teaching model was implemented in the experimental group, while the 5E teaching model, typically used in a normal classroom was employed in the control group. Two types of tests, namely the mathematical literacy test and the mathematical problem-solving test, were used as research instruments. Pre and post-data were collected from both the experimental and control groups. Repeated measures ANOVA with Wilks’ lambda was employed to analyze the mean comparison for mathematical literacy and mathematical problem-solving. Findings - The findings revealed that the mean scores for mathematical literacy and mathematical problem-solving were relatively higher in the STEMEN teaching model group compared to the 5E teaching model group. These results provide insights into the effectiveness of the STEMEN teaching model in enhancing learning outcomes, particularly mathematical literacy and problem-solving in mathematics. Significance – The results of this study showed that the STEMEN teaching model was effective in increasing learning outcomes, including mathematical literacy and problem-solving. These outcomes should enable teachers to design effective and efficient instructional strategies for enhancing mathematical literacy and problem-solving in classrooms.